2023
DOI: 10.1001/jamanetworkopen.2023.0806
|View full text |Cite
|
Sign up to set email alerts
|

Association of the End-Stage Renal Disease Treatment Choices Payment Model With Home Dialysis Use at Kidney Failure Onset From 2016 to 2022

Abstract: ImportanceThe Centers for Medicare & Medicaid Services designed a mandatory payment model to incentivize home dialysis use: the End-Stage Renal Disease Treatment Choices (ETC). Outpatient dialysis facilities and health care professionals providing nephrology services were randomly assigned to ETC participation at the hospital referral region level.ObjectiveTo assess the association between ETC and home dialysis use in the incident dialysis population in its first 18 months of implementation.Design,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Whether financial incentives encourage physicians to increase prescription of home dialysis is uncertain 26 ; early analyses of the ETC model suggest a modest effect. 27,28 The costs of operating a home dialysis program are driven by staff and supply costs, including machines, dialysate, and disposable supplies. Ongoing contractual negotiations with home dialysis device and supply manufacturers are needed to ensure financial sustainability, to maintain a reliable supply chain, and to arrange additional support services.…”
Section: Economicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether financial incentives encourage physicians to increase prescription of home dialysis is uncertain 26 ; early analyses of the ETC model suggest a modest effect. 27,28 The costs of operating a home dialysis program are driven by staff and supply costs, including machines, dialysate, and disposable supplies. Ongoing contractual negotiations with home dialysis device and supply manufacturers are needed to ensure financial sustainability, to maintain a reliable supply chain, and to arrange additional support services.…”
Section: Economicsmentioning
confidence: 99%
“…Whether financial incentives encourage physicians to increase prescription of home dialysis is uncertain 26 ; early analyses of the ETC model suggest a modest effect. 27,28…”
Section: Patient Trainingmentioning
confidence: 99%
“…11 A recent analysis explicates the financial incentives of the ESRD Treatment Choices Model, which appear to have successfully increased home dialysis use and initiation. 12 These innovative models served as a call for valuebased care (VBC) in the nephrology community. Yet despite their benefit enhancements, aligned incentives, and impact potential, emerging kidney care models remain in an early stage of development.…”
Section: Introductionmentioning
confidence: 99%
“…Most prominently, the Model challenged the kidney care industry's status quo of in‐center dialysis and delayed transplantation—standards which adversely impact patient quality of life and health system cost burden 11 . A recent analysis explicates the financial incentives of the ESRD Treatment Choices Model, which appear to have successfully increased home dialysis use and initiation 12 …”
Section: Introductionmentioning
confidence: 99%
“…2 The ETC is among the largest randomized tests of pay-for-performance incentives ever conducted in the US. Two prior evaluations have reported that the ETC model was associated with an increase 11 (among all adult incident patients) or no change 12 (among incident traditional Medicare beneficiaries ≥66 years) in home dialysis use. No prior study has examined the consequences of the ETC model on equity in kidney failure treatment.…”
mentioning
confidence: 99%